2019
DOI: 10.1186/s40246-019-0192-8
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for the use of Cre recombinase for conditional gene deletion in the mouse lens

Abstract: Background Despite a number of different transgenes that can mediate DNA deletion in the developing lens, each has unique features that can make a given transgenic line more or less appropriate for particular studies. The purpose of this work encompasses both a review of transgenes that lead to the expression of Cre recombinase in the lens and a comparative analysis of currently available transgenic lines with a particular emphasis on the Le-Cre and P0-3.9G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…Pairing these techniques with CAV and intersectional methods enables a wide range of combinations, allowing substantial versatility and creativity in experimental designs. It should be noted that, regardless of the vector used, long-term overexpression of Cre recombinase can be toxic (Silver and Livingston, 2001;Braz et al, 2002;Whitsett and Perl, 2006;Gong et al, 2007;Harno et al, 2013;Janbandhu et al, 2014;Lam et al, 2019), and therefore, precautions are needed when Cre is used in functional assays.…”
Section: Applicationsmentioning
confidence: 99%
“…Pairing these techniques with CAV and intersectional methods enables a wide range of combinations, allowing substantial versatility and creativity in experimental designs. It should be noted that, regardless of the vector used, long-term overexpression of Cre recombinase can be toxic (Silver and Livingston, 2001;Braz et al, 2002;Whitsett and Perl, 2006;Gong et al, 2007;Harno et al, 2013;Janbandhu et al, 2014;Lam et al, 2019), and therefore, precautions are needed when Cre is used in functional assays.…”
Section: Applicationsmentioning
confidence: 99%
“…Our results indicate that Gclc appears to be required for normal eye and lens development. However, Le-Cre transgenic mice can display a microphthalmia phenotype, regardless of floxed alleles [3639]. Therefore, the extent to which hemizygosity for the Le-Cre causes microphthalmia in our B6/FVB mixed background mice was determined (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given that the Le-Cre transgene utilizes the Pax P0 promoter, others have postulated that it may deplete cofactors required for endogenous Pax6 expression [37]. However, a recent study was unable to confirm this hypothesis [36]. Instead, it was found that the microphthalmia phenotype (in Le-Cre homozygous mice) was caused by changes in the expression of genes involved in the negative regulation of cell proliferation and cell growth, and positive regulation of apoptosis pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations